The hyoid arch and braincase anatomy of Acanthodes support chondrichthyan affinity of ‘acanthodians’ - Brazeau,MD; de,Winter V (Proceedings of the Royal Society B: Biological Sciences, 2015)
Solving the evolutionary relationships of the acanthodians is one of the key problems in reconstructing ancestral anatomical conditions for the jawed vertebrates (gnathostomes). Current debate concerns whether acanthodians are an assemblage of stem chondrichthyans, or a more generalized grade encom- passing some early stem osteichthyans. The skull anatomy of Acanthodes bronni has been pivotal in these debates, owing to tension between chondrichthyan- and osteichthyan-like models of reconstruction. We use computed tomography scanning and traditional palaeontological techniques to resolve the long- standing debate about the anatomy of the jaw suspension. We establish the correct length of the hyomandibula and show that it attaches to a process on the ventrolateral angle of the braincase below the jugular vein groove. This condition corresponds precisely to that in chondrichthyans. This character represents an unambiguously optimized synapomorphy with chondrichthyans given current gnathostome phylogenies, corroborating the growing consensus of the chondrichthyan affinity of acanthodians.